The Use of Animated Video to Improve Students’ Writing Ability at SMP Negeri 1 Tabongo - Tiara H. Husain; Dewi Dama; Rahmawaty Mamu (Transbahasa, 2025)
This study aims to investigate the effectiveness of using animated videos to improve the narrative writing ability of ninth-grade students at SMP Negeri 1 Tabongo. The research employed a quantitative approach with a pre-experimental design (one group pre-test and post-test). The participants consisted of 17 students from class IX-B selected through purposive sampling. The instrument used was a writing test administered before and after the treatment, assessed based on five aspects: organization, content, grammar, punctuation, and style. The treatment was conducted over four session, with a different stages: story introduction, discussion, vocabulary reinforcement, and writing practice. The statistical analysis using a t-test showed a significant improvement in students’ writing ability after the treatment. The average score increased from 55 (pre-test) to 70 (post-test), with a significance value of p < 0.05. Classroom observations also revealed increased student participation, better understanding of narrative text structure, and enhanced writing motivation. In conclusion, the use of animated videos proved to be an effective medium for improving students’ narrative writing skills. This media not only enhances students’ understanding of text structure but also fosters emotional engagement and motivation in the writing learning process.